2021
DOI: 10.1016/j.xrrt.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid achieves less blood loss volume of in primary shoulder arthroplasty: a systematic review and meta-analysis of level I randomized controlled trials

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
(206 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have underscored the effectiveness and safety of TXA in reducing blood loss during total joint arthroplasty (TJA). Its routine use has been linked to reduced postoperative bleeding and lower transfusion requirements [6][7][8][9][10][11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have underscored the effectiveness and safety of TXA in reducing blood loss during total joint arthroplasty (TJA). Its routine use has been linked to reduced postoperative bleeding and lower transfusion requirements [6][7][8][9][10][11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%
“…There is a debate in the literature on the optimal regimen of TXA administration. TXA can be administered intravenously, topically, orally, or by multiple routes 1,12,13,15 . Intravenous (IV) administration of TXA has become a standard practice to prevent perioperative blood loss in total knee arthroplasty (TKA) and total hip arthroplasty 18 .…”
mentioning
confidence: 99%
“…The efficacy and safety of tranexamic acid (TXA) in hip and knee replacement has been extensively studied in the orthopedic department of our hospital [1][2][3][4][5] , and studies have shown that TXA can obviously reduce blood loss and transfusion rate during the perioperative period in total hip and total knee replacement. It has also been reported that the use of TXA in shoulder replacement can reduce perioperative blood loss and complications 6,7 , and the use of TXA in trauma orthopedics and spinal fusion can also significantly reduce perioperative blood loss and related complications [8][9][10] . However, there are few reports on the application of TXA in total ankle replacement (TAR), and the conclusions of the two existing studies are completely opposite.…”
mentioning
confidence: 99%